2013
DOI: 10.17722/ijme.v1i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Corporate Scams on share prices: A study of Indian Stock market

Abstract: Abstract-This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In emerging markets like India, various studies have employed the event study methodology to analyse the reaction of specific stocks to various announcements such as earnings, Mergers and Acquisitions (M&A), and dividends. (see, e.g., Ahmad et al, 2022; Anwar et al, 2017; Arulsulochana et al, 2019; Belgaumi, 1995; Dawar & Goyal, 2013; Maitra & Dey, 2012; Mallikarjunappa & Dsouza, 2013; Manasseh et al, 2016). Various researchers have shown several studies to examine the effect of negative information announcements such as scams, frauds, crimes and more on stock prices.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In emerging markets like India, various studies have employed the event study methodology to analyse the reaction of specific stocks to various announcements such as earnings, Mergers and Acquisitions (M&A), and dividends. (see, e.g., Ahmad et al, 2022; Anwar et al, 2017; Arulsulochana et al, 2019; Belgaumi, 1995; Dawar & Goyal, 2013; Maitra & Dey, 2012; Mallikarjunappa & Dsouza, 2013; Manasseh et al, 2016). Various researchers have shown several studies to examine the effect of negative information announcements such as scams, frauds, crimes and more on stock prices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study found that if a company’s profits remained intact before and after correction, it would be considered in evaluating the stock price. Dawar and Goyal (2013) investigated the impact of corporate scams on companies’ share prices, prompted by recent scandals, including the Satyam scandal in India. Using an event study approach and data from eight companies, the study found that the market efficiently absorbed all the information about the scam, and its impact on stock returns was insignificant.…”
Section: Literature Reviewmentioning
confidence: 99%